รูปแบบการเดินทางของนักเรียนในสถาบันกวดวิชาบริเวณโดยรอบสี่แยก พญาไท - นธิดา กลัดสำเนียง (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research is to study travelling patterns of students in tutorial institutes around Phayathai crossroads area since their origin to the destinations and also to collect and make correctly understanding to all of factors or problems effecting to each travelling pattern. The result can lead to efficient transportation management and planning between public transportation interconnection and telecommunication network consistency, by studying the travelling patterns and also observing the basis structure of transportations that related the each pattern. Students’ behavior and preference, distribution of location of both beginning points and destinations are also observed and studied leading to advise a suitable travelling pattern. As the result, found that there is variety of travelling patterns of student in weekend class (Saturday-Sunday) many more than student in weekdays class (Monday-Friday). From the difference of beginning points and destination of both weekdays and weekend classes, found that economical factor, telecommunication system availability, public transportation and time are the most important factors that significantly effect to travelling patterns of student in weekend class. Reversely, the time limitation is only one factor of student in weekday class. However the patterns of students in tutorial institutes around Phayathai crossroads area can indicate the efficiency of the present public transportations and telecommunication system correctly. Eventually, the practical advice based on the research result, pointed at fundamental public transportation and request government to improve and furnish the telecommunication system availability.